BS ISO/IEC 15944-16. Information technology. Business operational view. Part 16. Consolidated set of the rules and guidelines identified in ISO/IEC 15944 Business Operational View standards and their IT-enablement (8th March 2021) - British Standards Institution,
No abstract available